Comparison of surface properties of DLC and ultrananocrystalline diamond films with respect to their bio-applications - Jelinek, Miroslav; Voss, Alexandra; Kocourek, Tomáš; Mozafari, Mahsa; Vymetalová, Veronika; Zezulová, Marketa; Písarík, Petr; Popov, Cyril; Mikšovský, Jan (International Conference on Plasma Surface Engineering, 2013)
DLC layers are entirely amorphous or contain micro- or nanocrystalline diamond or graphite and possess a disordered structure with a mixture of carbon bonding configurations. Furthermore, DLC can be hydrogen free (a-C) or containing hydrogen (hydrogenated amorphous carbon (a-C:H)). DLC films exhibit excellent physical and chemical properties, as well as high level of biocompatibility [1]. The films are dense, mechanically hard, smooth, abrasion resistant, IR transparent, chemically inert, resistant to attack by both acids and bases, have a low coefficient of friction, low wear rate, and are biocompatible and thromboresistant [2-3]. DLC coatings can be adherent on various biomaterials; neither toxicity toward certain living cells nor inflammatory response or loss of cell integrity were reported [4]. DLC shows an excellent hemocompatibility, a decreased tendency of thrombus formation and coated heart valves and stents are already commercially available [5]. The properties of the DLC coatings depend strongly on the hydrogen content and sp3/sp2 ratio which, in turn, depend on the deposition process and its parameters. The range of the properties of the DLC produced by different methods and under different process parameters is considerable. Diamond is a material with quite a number of excellent properties [6], like extreme hardness, high elastic modulus, high wear resistance, optical transparency in a broad spectral range, resistivity controllable by the level of dopants, etc. which make it a promising candidate for diverse applications. Due to its outstanding electrochemical properties, superior chemical inertness and biocompatibility, artificially grown diamond has been recognised as an extremely attractive material for both (bio-)chemical sensing and as an interface to biological systems. This holds for all forms of diamond: monocrystalline (natural or artificial) and poly- (PCD), nano- (NCD) and ultrananocrystalline (UNCD) films. In the current work the surface and antibacterial properties of DLC and UNCD films including the nature of the surface bonding and termination, wettability, surface energy and tests with Gram-positive and Gram-negative bacteria were studied and discussed.